2016
DOI: 10.3390/su8080769
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Incentive Policies for Building-Integrated Photovoltaic Technology in Hong Kong

Abstract: Abstract:Installing sustainable and renewable energy systems is a promising way of relieving Hong Kong's dependence on imported fossil fuels. Solar photovoltaic (PV) technology is a perfect solution for Hong Kong as it fits the economic and geographic situation. Through a review of the PV development history of five leading PV countries, Germany, Japan, Italy, Mainland China, and the USA, this paper serves as a useful policy toolbox to aid PV development. Based on the forerunners' successful PV industry experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Researchers built theories on how incentive policies promote innovation development by analyzing the status quo and existing problems of industry (or industry development). For example, Song et al [20] analyzed the situation and experience of the photovoltaic industry and proposed a series of incentive strategies to help enhance development of the industry. Zou et al [21] analyzed the development of China's green building and found that local economic fundamentals and subsidy-based incentive policies can explain the presence of green buildings.…”
Section: Previous Research On Transmission Mechanisms Of Incentivesmentioning
confidence: 99%
“…Researchers built theories on how incentive policies promote innovation development by analyzing the status quo and existing problems of industry (or industry development). For example, Song et al [20] analyzed the situation and experience of the photovoltaic industry and proposed a series of incentive strategies to help enhance development of the industry. Zou et al [21] analyzed the development of China's green building and found that local economic fundamentals and subsidy-based incentive policies can explain the presence of green buildings.…”
Section: Previous Research On Transmission Mechanisms Of Incentivesmentioning
confidence: 99%
“…Namely, the PV industry could be rapidly developed with sufficient financial support from the government, while it could decrease if the government reduced the financial support. In Japan, the government subsidy program in 1994 significantly lowered the PV installation cost, leading to a notable increase in the PV market [30,31]. Then, the PV subsidy was terminated during 2005-2008; accordingly, the installed capacity decreased from 290 MW to 225 MW.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [13] the PV temperature (T PV ) is derived from I o = BT 3 PV e −E g /(kT PV ) , where I o is the is the reverse saturation current of the diode PV model, E g is the band gap of silicon, and B is a temperature-independent constant. Notton el at.…”
Section: Pv Module Performancementioning
confidence: 99%
“…These characteristics have led many countries to pay attention on the design policies, strategies, and technology for its use [1][2][3][4]. In this context, photovoltaic (PV) systems are one of the most mature solar technologies, and it is constantly increasing its competitiveness and decreasing its production costs [5].…”
Section: Introductionmentioning
confidence: 99%